EVALUASI PROGRAM PEMBERDAYAAN MASYARAKAT: SUATU ANALISIS DALAM PERSPEKTIF PEMBERDAYAAN MASYARAKAT - Cornelius Herdita Aries Permana; Daru Purnomo (Universitas Kristen Satya Wacana, 2014)
Community empowerment are intended to be competitive and independent society, that means the community can learn from and implement community development programs independently to empower themselves. The purpose of this study was to evaluate the success of community empowerment programs conducted by Trukajaya in Lembu village and analyze the factors that affect the results of the implementation of the program based on community empowerment perspective. This study used a qualitative approach and included in the case study research. Based on the community development perspective, the program has not been successful, but not entirely fail because it is caused by several things, among others: First, community empowerment program implemented by Trukajaya yet to reduce the number of poor people in Lembu village. Second, community empowerment program implemented by Trukajaya not enough to help poor people in developing revenue enhancement initiatives, leveraging available resources. Third, community empowerment program implemented by Trukajaya successfully added concern of community efforts to improve well-being of poor families in the region. Fourth, community empowerment program implemented by Trukajaya not been able to increase the survival of the group. Fifth, community empowerment program implemented by Trukajaya not been able to fully enhance community capacity and equalize income because the income of poor families did not increase significantly. Keywords: programevaluation, community empowerment